How does quasi-indexer ownership affect corporate tax planning? - Chen, Shuping; Huang, Ying; Li, Ningzhong; Shevlin, Terry (Journal of Accounting and Economics, 2019)
We study whether, and more importantly, through what mechanisms, quasi-indexers affect portfolio firms’ tax planning by employing the discontinuity in quasi-indexer ownership around the Russell 1000/2000 index cutoff. Using a regression discontinuity design, we find that higher quasi-indexer ownership leads to greater tax saving. With respect to the mechanisms, we find that the greater tax saving is a result of a focus on improved overall firm performance, not a specific focus on improved tax planning. We further find that the documented tax saving effect is partially due to quasi-indexers’ influences on executive equity incentives, corporate governance, and information environment.